Kookaburra cricket bats : dealing with cannibalization - Hennessy, Julie ([London] : SAGE, 2016)
This exercise is one in a series intended to help students learn how to perform financial calculations in marketing contexts. Kookaburra, a maker of cricket equipment popular in Australia, New Zealand, the United Kingdom, South Africa, and India, was considering two strategies for positioning a new cricket bat in India. Both strategies would cannibalize current sales, and Lulu Popplewell, category manager responsible for the Indian market, needed to calculate the financial impact of both to determine which one she would recommend. This exercise poses a fictional problem about branding strategy on a new product, and asks students to consider the financial impact of different branding strategies and cannibalization rates.
Originally Published in: Hennessy, J. (2012). Kookaburra Cricket Bats: Dealing with Cannibalization (Case revised 15/12/2014). 3-112-002. Evanston, IL: Kellogg School of Management at Northwestern University.
Description based on online resource; title from home page (viewed on April 27, 2016).
Keywords: elektronické knihy; electronic books; Kookaburra (Firm); New products -- Marketing -- Case studies; New products -- Management -- Case studies; Business forecasting -- Case studies